Democracy and truth: A cluster of problems an attempt to sort them out - Stupar Milorad (Belgrade Philosophical Annual, 2014)
This paper attempts to show that an idea of truth and a normative liberal democratic theory can go hand in hand. First, it is argued that truth has something to do with politics. Second, three possible aspects of the relationship between democratic government and truth are discussed. The discussion begins with a presentation of arguments for the view that the process of establishing scientific truth stricto sensu is not generally a matter of wide public or democratic debate, and thus is not incompatible with a democratic order. The discussion then moves on to consider practical social problems; it ends with the claim that unlike in 'pure' scientific inquiry, democratic procedure is directly relevant and perhaps crucial to solving practical collective problems. The final part of the paper concerns 'the market of ideas' and the possibility of its failure. It is clear that market of ideas is not sufficient for producing autonomous and critical citizens who have a 'strong desire not to be fooled' (Bernard Williams). Quite the contrary, the marketplace of ideas may be exposed to agencies that deliberately distort and conceal the truth. Governments are prone to commit such illegitimate actions because of the very nature of their ways of working. This may be the most difficult problem for a democratic institutional framework.